The Role Healthy Sexuality Plays in Modifying Abusive Behaviours of Adolescent Sex Offenders: Practical Considerations for Professionals - Perry, Garry P.; Ohm, Phyllis (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper highlights an approach that guides adolescents who have committed sexual offences to learn healthy/prosocial ways to meet their sexual needs. This paper is divided into an overview of literature, review of the sex education component of an intervention program for adolescent sex offenders, and a discussion on the practical considerations for professionals working with adolescent sex offenders. The information has a direct applicability to professionals working with adolescent sex offenders or with non-offending youths. Themes of healthy lifestyle and healthy choices are stressed.